Some ideas to minimize an empirically given fuzzy function - Bandemer, H. (Optimization, 1991)
In real world problems, usually, the response variable as well as the adjustable control variables are subject to vagueness and uncertainty. These properties can be taken into account by means of specifying fuzzy sets for the respective values. In the paper the case is considered that the function to be minimized is a fuzzy one and can only be inspected point by point. Then a region is to be found where the values of the response variables are minimum in a given sense. Hence a sequential procedure is sketched for which the observed values will run into such a region.